STUDY OF ADDITIVE MANUFACTURING OF ELECTRICALLY CONDUCTIVE POLYMER COMPOSITES - FEDORIV, TARAS; SLIEPTSOV, ALEXANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is dedicated to the study of the influence of parameters of additive manufacturing by the method fused filament fabrication on the electrical properties of conductive polymer composite. The specific surface electrical resistivity was determined by the four-electrode method, and the density was determined by hydrostatic weighing according to ISO 1183. Consumable material in form of filament was created by twin-screw extruder compounding and single screw extrusion process. Prototypes were manufactured using a Bambu-Lab A1 mini additive manufacturing device. Different type carbon base fillers was used in the study – pigment grade carbon black (Kremenchug technical carbon plant N330), conductive grade carbon black (Cabot Vulcan XC72)  and industrial grade multi walled carbon nanotubes (Nanocyl NC7000), which was compounded in thermoplastic polyurethane polymer matrix (Laripur  9025).  The resistivity values were measured for different samples in the form of composite, monofilament, and the sample after additive manufacturing. It was found that the specific surface electrical resistivity of all considered composites increases during sequential processing. The influence of the parameters of additive manufacturing by the method of fused filament fabrication on the electrical properties of conductive polymer composite based on thermoplastic polyurethane filled with carbon black and carbon nanotubes was investigated. It has been found that the samples obtained by additive manufacturing have a pronounced anisotropy of the surface electrical resistance value measured relative to the direction of the material jets orientation during layer formation. It has been found that the surface electrical resistance of the first and last layers of the sample are significantly different, which is probably due to the cooling conditions during the formation of these layers of the sample. A significant anisotropy of the surface electrical resistance relative to the direction of material flow in the layers was found. Significant differences in the resistivity values of the samples in the first and last layers were found. The technological modes of additive manufacturing of products by the method of layer-by-layer surfacing of plastic from a composite based on thermoplastic polyurethane filled with carbon black and carbon nanotubes have been worked out.
Keywords: additive manufacturing; conductive polymer composite; thermoplastic polyurethane; conductive filler; carbon black; carbon nanotubes